Production of nanoscale Ba(Zn1/3Nb2/3)O-3 microwave dielectric ceramics by polymerised complex method - (:unkn) unknown (ELSEVIER SCIENCE SA, 2009)
Ba(Zn1/3Nb2/3)O-3 nanoparticles have been synthesized by a polymerised complex method by using precursor materials of barium nitrate, zinc acetate, niobium oxide, hydrofluoric acid and citric acid. Thermal decomposition characteristics and crystallization behavior of the powders were investigated by the thermogravimetric and differential thermal analysis, X-ray diffractometer and Fourier transform infrared spectroscopy. Ba(Zn1/3Nb2/3)O-3 phase started to form at low temperature of 400 degrees C and, single phase Ba(Zn1/3Nb2/3)O-3 perovskite structure was obtained at 1000 degrees C. Microstructural investigation revealed that the major particle size of Ba(Zn1/3Nb2/3)O-3 nano particles were in the range of 80-110 nm with spherical morphology and homogeneous size distribution. But the powders also contained some agglomeration. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ba(Zn1/3Nb2/3)O-3; Perovskite; Microwave dielectric ceramics; Citrate gel; RESONATORS; BEHAVIOR; PHASE